Developmental defects of enamel in children born preterm - Halperson, Elinor; Shafir, Salome; Fux-Noy, Avia; Ram, Diana; Eventov-Friedman, Smadar (Frontiers in Pediatrics, 2022)
Introduction: To investigate manifestations of developmental defects of enamel (DDE) in children born preterm (PT), and to explore possible neonatal morbidities related to DDE manifestation and severity. Methods: A cohort study of 52 children born before gestational week 32 and treated in the neonatal intensive care unit; and 55 children born at full term (FT) as a control group. All the children had a dental examination at age 1-4 years by a professional pediatric dentist. DDE was defined as an alteration in the enamel surface. Results: DDE were observed in 23 (44%) and 6 (11%) children, in the PT and FT groups, respectively, odds ratio (OR)=6.47. The OR for damaged anterior teeth was 12.87 times higher in the PT group. DDE of molars was diagnosed in 19% and 11% of the respective groups. In the PT group, the OR of DDE was 4.1 higher among those with than without respiratory distress. The risk for DDE was 5.7 higher in those who received surfactant than in those who did not. Ventilation length, both invasive and non-invasive, was significantly related to DEE. Conclusions: DDE was higher in children born PT than FT. The DDE rate was lower than expected based on current literature, and considering the overall increase in survival; this suggests improvement in treatments affecting DEE. Respiratory distress syndrome, surfactant administration reflecting the need for intubation, longer ventilation and local oral trauma were risk factors for DDE. We recommend routine dental examinations in follow up of children born PT, particularly those exposed to assisted ventilation.